قانون منع الميسر فى ولاية أتشيه : دراسة تحليلية نقدية فى ضوء مقاصد الشريعة الإسلامية - حسن, ميسرة رحمي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study examines the law of gambling and its application in Aceh Indonesia. The study makes an attempt to explore the concept of gambling and the emergence of gambling in pre- Islamic time with its types and configuration, gambling attend and advent of Islam, and evidence of its prohibition, the wisdom behind its prohibition, benefits and damage of gambling. It also explains the concept of objectives of Islamic law and the purpose of financial transaction, the benefits and harms of gambling, the purposes of Islamic law in the prohibition of gambling. In addition, it explains the application of law on prevention of gambling in Aceh corresponding to the objectives of Islamic law in its implementation and application in Aceh. At the end, the study presents the benefit of this application and its possibility, the punitive punishment for who those gamble and its application in Aceh, the position of Aceh's government to apply this punishment, and the study cases of cane in Aceh especially for who those violate the law of gambling. The research problem is general lack of understanding of Aceh community about the application of the law on gambling to be part of divine law. The research adopts descriptive and inductive analytical approach to reach the desired results. The researcher concluded from this study that the purpose of Islamic law in prohibit of gambling is appropriate with Aceh governments application of the law on prevention of gambling in Aceh for conserving the five basic objectives of Islamic law, since gambling brings many harms as explained by many evidences from Qur'an and Sunnah. An important finding in this study is that gambling still exists in Aceh, and the Government is still trying to eliminate it, because that action is not legal, and Muslim must avoid it. The purposes of this law are to protect money, and spend it in correct way, since the preservation of property is one of the five basic objectives of Islamic law.